2011
DOI: 10.1519/jsc.0b013e3181c7bac6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Biomarker Responses To an Acute Session of Hypertrophy-Resistance Traditional Interval Training and Circuit Training

Abstract: We have studied circuit resistance schemes with high loads as a time-effective alternative to hypertrophy-traditional resistance training. However, the oxidative stress biomarker responses to high-load circuit training are unknown. The aim of the present study was to compare oxidative stress biomarker response with an acute session of hypertrophy-resistance circuit training and traditional interval training. A week after the 1 repetition maximum (1RM) test, 11 healthy and well-trained male participants complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
1
13
1
7
Order By: Relevance
“…Thus, besides greater lactate production, it was expected that the TM induced to greater muscle damage when compared with the CM. Deminice et al 30 after having compared the TM performed with three sets, 10 repetitions, 75% of 1RM and 90 seconds of rest interval and the CM with similar work and without rest interval, observed that the methods are not significantly different compared with muscle damage, although both have presented increase in the creatine kinase enzymatic activity post-exercise. Thus, it seems that when the subjects are trained and the training methods are standardized by work, both CM and TM produce similar responses related to muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, besides greater lactate production, it was expected that the TM induced to greater muscle damage when compared with the CM. Deminice et al 30 after having compared the TM performed with three sets, 10 repetitions, 75% of 1RM and 90 seconds of rest interval and the CM with similar work and without rest interval, observed that the methods are not significantly different compared with muscle damage, although both have presented increase in the creatine kinase enzymatic activity post-exercise. Thus, it seems that when the subjects are trained and the training methods are standardized by work, both CM and TM produce similar responses related to muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown increased oxidative stress biomarkers after acute exercise in rats (Bachur et al 2007) and humans (Michailidis et al 2007;Deminice et al 2011). The extent of oxidation is dependent on the exercise mode, intensity, and duration (Bloomer 2008).…”
Section: Introductionmentioning
confidence: 99%
“…41 Egzersiz sırasında SR üretimi egzersizin tü-rüne, şiddetine ve süresine bağlıdır. [44][45][46] Bunun en önemli sebebi, farklı egzersiz türlerinin farklı enerji gereksinimlerinin olması ve bundan dolayı farklı oksijen tüketim seviyelerine neden olmasıdır. Bunun sonucunda dokularda oluşturdukları farklı mekanik streslerin etkisi ile farklı kaynaklardan SR üretimini tetiklemesidir.…”
Section: Egzersi̇z Ve Oksi̇dati̇f Stresunclassified